Association between depressive symptoms and adherence to highly active antiretroviral therapy in HIV-positive women is dependent of menopausal status: a secondary analysis from a Peruvian series - Arriola Montenegro, José (2019)
The adherence to highly active antiretroviral therapy (HAART) is key to the therapeutic success of HIV patients and associated to depressive symptoms (DS) in several studies. However, there are few publications regarding mid-aged women; a period in which the menopausal status could play an important role.